Pengaruh Pemberian Nanopartikel TiO₂ pada Berbagai Konsentrasi terhadap Perubahan Morfologi dan Biomassa Kalus Ginseng Jawa (Talinum paniculatum) secara In Vitro - Maulana, Zakiy; Noli, Zozy Aneloi; Suwirmen; Fajrisani, Syifa; Putri, Suci Indah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the effect of titanium dioxide (TiO₂) nanoparticle concentrations on the characteristics of Talinum paniculatum (Java ginseng) callus. The experiment was conducted using a completely randomized design with six TiO₂ concentration treatments (0, 1, 2, 3, 4, and 5 ppm) over a 14-day incubation period. The observed parameters included callus morphology (color and texture), fresh weight, and dry weight. Fresh and dry weight data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan’s New Multiple Range Test (DNMRT), while callus color and texture were analyzed descriptively. The results showed that the addition of TiO₂ nanoparticles induced changes in callus color ranging from yellow to yellow-reddish, and the resulting callus exhibited a compact texture. TiO₂ nanoparticles up to a concentration of 5 ppm did not show negative effects on either fresh or dry callus weight. These findings indicate that TiO₂ nanoparticles at the tested concentrations play a role in modifying the visual characteristics of callus without affecting biomass accumulation. Therefore, TiO₂ nanoparticles have potential application in enhancing secondary metabolite production.